Использование налогово-бюджетных инструментов развития социальной сферы регионов в условиях неоиндустриализации - Вишневский, В.П.; Чекина, В.Д.; Виецкая, О.В. (Економіка промисловості, 2016)
Рассмотрены концептуальные положения использования налогово-бюджетных инструментов для обеспечения развития социальной сферы регионов, основанные на современной экономической теории децентрализации. Предложены направления децентрализации бюджетных доходов с учетом европейского вектора развития экономики Украины, которые будут способствовать повышению степени финансовой автономии органов местного самоуправления и ускорению развития социальной сферы регионов. Розглянуто концептуальні положення використання податково-бюджетних інструментів для забезпечення розвитку соціальної сфери регіонів, які базуються на сучасній економічній теорії децентралізації. Запропоновано напрями децентралізації бюджетних доходів з урахуванням європейського вектора розвитку економіки України, які сприятимуть підвищенню ступеня фінансової автономії органів місцевого самоврядування і прискоренню розвитку соціальної сфери регіонів. Conceptual positions of the application of fiscal instruments with a view to ensuring the development of the social sphere of the regions based on the modern theory of economic decentralization have been considered. On the basis of the principles of fiscal balance and subsidiarity the allocative powers that are advisable to assign to the different levels of sub-central government have been determined as well as the appropriate revenue sources that are able to provide funding for these powers. The distribution and financial provision of the powers of sub-central authorities have been examined by the example of the European experience, which is founded by the choice of the European vector of social and economic reforms in Ukraine. It has been established that in a situation of recession or slowdown in economic growth the decentralization opportunities related to the transfer of spending authority to the local governments are limited. And conversely, prolonged periods of economic recovery that occurred in recent decades in many EU countries as a whole have contributed to decentralization processes. The structure and revenue sources of the sub-central authorities in particular countries of the European Union have been studied, the degree of their fiscal autonomy has been determined. It was found that in cases of the division of powers between the central government and sub-central authorities connected with provision of social services (which are characterized by a "blurred" sphere of benefits and the presence of significant external effects) it is necessary to follow the requirements of the economic theory of decentralization. It is proved that the key proposition of fiscal decentralization at the present stage of development of the Ukrainian economy should be focused on the decentralization of budget revenues aimed at increasing the relative importance of own sources of sub-central authorities at the expense of increasing their tax opportunities and reducing the volume of inter-budgetary transfers. For this purpose it is advisable to analyze and revise the current distribution of the tax powers and the tax bases between the levels of government taking into account the major conceptual and administrative provisions of the economic theory of decentralization aimed at the increasing the real degree of sub-central financial autonomy.